A study of the effects of climate change and human activities on NPP of marsh wetland vegetation in the Yellow River source region between 2000 and 2020 - Feng, Xueke; Zhao, Zhizhong; Ma, Tao; Hu, Bixia (Frontiers in Ecology and Evolution, 2023)
The Yellow River source region represents a typical alpine marsh wetland distribution area in the world. Since 2000, the marsh wetland in this region have undergone varying degrees of restoration and degradation as a result of climate change and human activities. Net primary productivity (NPP) is an effective indicator to characterize vegetation dynamics and carbon sequestration capacity, which allows one to quantify the effect of climate change and human activities on the wetland ecosystem. In this study, the potential and actual net primary productivity (NPPp and NPPa) of marsh wetland vegetation in the Yellow River source region between 2000 and 2020 were stimulated using the Zhou Guangsheng model and MOD17A3, and the difference between them was employed to calculate the NPP affected by human activities. Besides, the relative contribution of climate change and human activities to the change of NPPa of marsh wetland vegetation was quantitatively evaluated. The results revealed that between 2000 and 2020, NPPa of marsh wetland vegetation increased in the Yellow River source region by 95.76%, among which the contribution of climate change was 66.29%, and that of human activities was 29.47%. The Zoige Plateau in the southeast accounted for the majority of the 4.24% decline in the NPPa of the marsh wetland vegetation, almost all of which were affected by human activities. It is found that the warming and humidifying of climate, as well as human protective construction activities, are the important reasons for the increase of NPPa of marsh wetland vegetation in the Yellow River source region. Although climate change remains an important cause of the increase in NPPa of marsh wetland vegetation, the contribution of human activities to the increase in NPPa of marsh wetland vegetation is increasing.